China's Interannual Variability of Net Primary Production Is Dominated by the Central China Region. Issue 4 (17th February 2021) - Peng, Jing; Dan, Li; Ying, Kairan; Yang, Shuai; Tang, Xiba; Yang, Fuqiang
Abstract: It is important to understand regional contributions to interannual and decadal variabilities of vegetation productivity. However, most studies of regional terrestrial carbon cycles focus on the contributions of regional ecosystems to the mean or trend of net primary production (NPP), rather than its interannual variability (IAV). In this study, the IAV of NPP is explored using the simulation of the Australian Community Atmospheric Biosphere Land Exchange model, version 2.1 (CABLE2.1), compared with an eight‐member Trends in Net Land–Atmosphere Carbon Exchanges (TRENDY) ensemble under present conditions (1951–2010). NPP IAV is also analyzed using only CABLE2.1 under future conditions (2041–2100). Under the present conditions, the Central China region (region CC) contributes the largest fraction (CABLE2.1, 28.2%; TRENDY, 33.3% ± 11.5%) of NPP IAV in China. Such an NPP IAV is strongly associated with circulation‐driven variations in precipitation in most of China (∼85%). During the future period, region CC still plays a key role in the national NPP IAV, at ∼24.6%. Although precipitation IAV is still the main driver regulating the NPP IAV for region CC under the future conditions, climate sensitivity of NPP IAV to precipitation IAV may weaken compared with those under the present conditions. Our results highlight the contribution of region CC to the NPP IAV of China as a whole. Key Points: China's interannual variability (IAV) of net primary production (NPP) is dominated by the Central China region (region CC) under present and future conditions NPP IAV in China is strongly associated with the variability of precipitation rather than temperature High precipitation IAV may be the largest contributor to the national NPP IAV for region CC